ANALISIS POLITIK HUKUM TENTANG PASAL KARET UU ITE 2008 - Aulia, Mohamad Donie; Zultaqawa, Zeis (Majalah Ilmiah UNIKOM, 2025)
ABSTRACT This study aims to analyze the role of legal politics and the function of law in the Electronic Information and Transactions Law (UU ITE), as well as to examine the understanding of cyberspace, cybercrime, cyber law, the existence of multi-interpretative provisions, and their implementation in Indonesia. The research employs a normative juridical approach through literature review, with data analysis conducted using deductive reasoning. The findings indicate that UU ITE, as a legal product, is influenced by political dynamics, social conditions, and the development of information technology. From 2008 to 2021, its enforcement has implicated hundreds of internet users, primarily through Articles 27, 28, and 29, which are considered multi-interpretative. Revisions to UU ITE have not fully addressed public demands for the protection of freedom of expression and have left several problematic provisions due to limited public participation. Meanwhile, the rising number of cybercrime cases, such as defamation, hate speech, and hoaxes, highlights the urgency of effective cyber law regulation. The implications of this study emphasize the need to reformulate multi-interpretative provisions to prevent legal uncertainty and to ensure freedom of expression. Furthermore, strengthening digital legal literacy and socialization of UU ITE is essential to prevent violations in cyberspace. The government must develop more adaptive, transparent, and participatory cyber law regulations to provide legal certainty and justice in response to the rapid growth of information technology. Key Words: UU ITE 2008, Rubber Articles, Cyber Law, Cybercrime